Withdrawal of alcohol promotes regression while continued alcohol intake promotes persistence of LPS-induced pancreatic injury in alcohol-fed rats. Issue 2 (24th September 2010) - Vonlaufen, Alain; Phillips, Phoebe A; Xu, Zhihong; Zhang, Xuguo; Yang, Lu; Pirola, Romano C; Wilson, Jeremy S; Apte, Minoti V
Abstract : Background and aims: Administration of repeated lipopolysaccharide (LPS) injections in alcohol-fed rats leads to significant pancreatic injury including fibrosis. However, it remains unknown whether alcoholic (chronic) pancreatitis has the potential to regress when alcohol is withdrawn. The aims of the study were (1) to compare the effect of alcohol withdrawal/continuation on pancreatic acute injury and fibrosis; and (2) to assess the effects of alcohol ± LPS on pancreatic stellate cell (PSC) apoptosis in vivo and in vitro. Methods: Rats fed isocaloric Lieber–DeCarli liquid diets ± alcohol for 10 weeks were challenged with LPS (3 mg/kg/week for 3 weeks) and then either switched to control diet or maintained on an alcohol diet for 3 days, 7 days or 3 weeks. Pancreatic sections were assessed for acute tissue injury, fibrosis, PSC apoptosis and activation. Cultured rat PSCs were exposed to 10 mM ethanol ± 1 μg/ml LPS for 48 or 72 h and apoptosis was assessed (Annexin V, caspase-3 and terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL)). Results: Withdrawal of alcohol led to resolution of pancreatic lesions including fibrosis and to increased PSC apoptosis. Continued alcohol administration perpetuated pancreatic injury and prevented PSC apoptosis. Alcohol and LPS significantly inhibited PSC apoptosis in vitro, and the effect of LPS on PSC apoptosis could be blocked by Toll-like receptor 4 small interfering RNA. Conclusions: Induction of PSC apoptosis upon alcohol withdrawal is a key mechanism mediating the resolution of pancreatic fibrosis. Conversely, continued alcohol intake perpetuates pancreatic injury by inhibiting apoptosis and promoting activation of PSCs. Characterisation of the pathways mediating PSC apoptosis has the potential to yield novel therapeutic strategies for chronic pancreatitis.